Análisis del Tratado de Cielos Abiertos como mecanismo de impacto en el desarrollo económico de Ecuador - Cuenca Morocho., Emily Valentina (2024)
The present study, titled “Analysis of the Open Skies Treaty as a mechanism for impact on the economic development of Ecuador,” was conducted with the main objective of analyzing the economic impact generated by the Open Skies Treaty in Ecuador. Specifically, it aimed to analyze the impact, evolution, and comparative stage prior to its implementation and after that, in the national economy, providing important information on the contribution that the liberalization of the skies has made in Ecuador. To achieve this goal, a mixed research methodology was employed, which included reviews of secondary sources such as international treaties and laws related to civil aviation. As well as statistical data on tourism, foreign trade, and air cargo flow from government websites. This review allowed for the establishment of a solid conceptual framework and contextualization of the regulatory framework. The results indicate that the opening of new routes and new international airlines has boosted tourism, increasing the arrival of tourists. Additionally, it has increased trade and air connectivity, which has contributed to the country's economic growth. The triangulation of qualitative and quantitative data supported these conclusions, reinforcing the idea that open skies agreements have played a crucial role in the economic development of Ecuador by fostering competition, stimulating trade, and promoting global integration.